2015
DOI: 10.1016/j.dsr.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal and population connectivity in the deep North Atlantic estimated from physical transport processes

Abstract: 33Little is known about how larvae disperse in deep ocean currents despite how 34 critical estimates of population connectivity are for ecology, evolution and 35 conservation. Estimates of connectivity can provide important insights about the 36 mechanisms that shape patterns of genetic variation. Strong population genetic 37 divergence above and below about 3000m has been documented for multiple 38 protobranch bivalves in the western North Atlantic. One possible explanation for 39 this congruent divergence is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 136 publications
1
25
1
Order By: Relevance
“…The duration of simulation corresponded to the first PLD approximation of Aristeus antennatus larvae based on Penaeid larvae. The duration appeared to be shorter than PLD for other deep-sea species (Arellano et al, 2014: Etter andBower, 2015;Young et al, 2012) but was in agreement with PLD for temperate invertebrates (Levin and Bridges, 1995;Thatje et al, 2005;Williamson, 1982) and PLD of Penaeid species predicted in Dall (1990). Our study revealed interesting dispersal features, which could be related to the ecology of A. antennatus.…”
Section: Discussionsupporting
confidence: 70%
“…The duration of simulation corresponded to the first PLD approximation of Aristeus antennatus larvae based on Penaeid larvae. The duration appeared to be shorter than PLD for other deep-sea species (Arellano et al, 2014: Etter andBower, 2015;Young et al, 2012) but was in agreement with PLD for temperate invertebrates (Levin and Bridges, 1995;Thatje et al, 2005;Williamson, 1982) and PLD of Penaeid species predicted in Dall (1990). Our study revealed interesting dispersal features, which could be related to the ecology of A. antennatus.…”
Section: Discussionsupporting
confidence: 70%
“…A strictly allopatric explanation for the pattern of divergence observed with depth appears at odds with the fact that many invertebrates broadcast larvae capable of vertical travel in the open medium of the marine environment. Etter and Bower () modelled passive larval particle transport with depth along the US eastern seaboard to see whether current patterns in the region were a barrier separating shallower and deep populations in the region, but found this unlikely. Castelin et al.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise oceanographic simulations of deep-sea dispersal struggle with large uncertainties due to poor sampling of physical parameters in the deep sea and a lack of empirical data for calibration and groundtruthing of models (e.g. Young et al 2012;Sala et al 2013;Etter & Bower 2015;Hil ario et al 2015). Our database of genetic estimates of dispersal from IBD will help to advance such simulation work, which may in turn help to make our models of IBD in marine systems more realistic.…”
Section: Deep-sea Vs Shallow-water Dispersal Distancesmentioning
confidence: 99%